Management of School Guidance and Counseling Teachers in Addressing Student Delinquency at State Islamic Junior High School 2 Purwakarta - Asep Saepul Muslim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze and describe the management role of Guidance and Counseling (BK) teachers in addressing student delinquency at Madrasah Tsanawiyah Negeri 2 Purwakarta. Student delinquency in madrasah environments is a serious issue that significantly impacts the quality of education and the character development of students. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. Research informants included BK teachers, the madrasah principal, homeroom teachers, and involved students. Data analysis followed three interactive stages: data reduction, data presentation, and conclusion drawing. The findings reveal: (1) The management role of BK teachers at MTsN 2 Purwakarta is implemented through preventive actions including classical guidance, preservative actions directing students toward positive extracurricular activities, and curative actions including individual counseling and heart-to-heart communication; (2) Steps taken by BK teachers encompass personal approaches, categorization of delinquency types, provision of information services, group counseling, group guidance, and parental involvement for severe cases; (3) Obstacles faced by BK teachers include students' low self-awareness, unsupportive family backgrounds, and insufficient parental cooperation. This research affirms the importance of collaboration between BK teachers, homeroom teachers, school principals, and parents in shaping students' positive behavior.